Comparative Assessment of Advanced and Chinese Hybrid Lines of Wheat Under the Agro-Ecological Context of Peshawar, Pakistan - Subbuktageen Khan; Shamsur Rehman; Farzan Ullah; Muhammad Musa; Omar Farooq; Iftikhar Shah; Kareem Ashfaq; Nuiman Bin Zakir; Ubaid Ullah; Maleeha Mehboob (MultiTech Publisher, 2023)
The rate at which the world's population is expanding necessitates an annual increase in food production in order to feed the expanding population. As a result, during the Rabi season of 2021–2022, a field experiment was carried out at the Agronomy Research Farm, The University of Agriculture Peshawar. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. Row-Row spacing was kept at 30 cm. The experimental field was twice ploughed The evaluation was conducted employing eleven parameters, all of which were strongly influenced by different wheat lines. After an examination of the results, it was determined that the most desirable wheat line among the advanced lines in terms of biological and grain yield were AL-32 and AL-60 (8049 and 3610 kg ha-1, respectively), while the best performing line among Chinese hybrid lines in terms of biological and grain yield was 15-CA73 (9094 and 3777 kg ha-1, respectively), while the Khaista variety among local check varieties produced the highest biological and grain yield (5766 and 2277 kg kg ha-1, respectively). The rate at which the world's population is expanding necessitates an annual increase in food production in order to feed the expanding population. As a result, during the Rabi season of 2021–2022, a field experiment was carried out at the Agronomy Research Farm, The University of Agriculture Peshawar. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. Row-Row spacing was kept at 30 cm. The experimental field was twice ploughed The evaluation was conducted employing eleven parameters, all of which were strongly influenced by different wheat lines. After an examination of the results, it was determined that the most desirable wheat line among the advanced lines in terms of biological and grain yield were AL-32 and AL-60 (8049 and 3610 kg ha-1, respectively), while the best performing line among Chinese hybrid lines in terms of biological and grain yield was 15-CA73 (9094 and 3777 kg ha-1, respectively), while the Khaista variety among local check varieties produced the highest biological and grain yield (5766 and 2277 kg kg ha-1, respectively).